Energy efficiency practices in facilities management in Johannesburg. Issue 4 (2nd September 2019) - Adewunmi, Yewande Adetoro; Alister, Anthony; Phooko, Bopape; Nokukhanya, Thabethe
Abstract : Purpose: The purpose of this study is to examine at energy efficiency practices within the facilities management sector and barriers to adopting energy efficient strategies, it further explored the factors that promote the employment of energy efficient practices. Design/methodology/approach: The data were gathered by means of an electronic survey, administered to facilities managers in Johannesburg. Findings: Energy efficient lighting is the most used energy efficiency practice. It further uncovered that occupant engagement and education is considered least, amongst current energy efficiency practices. This study revealed that the biggest barrier to the implementation of energy efficient facilities management practices was the cost implications of adopting FM strategies and rated the lowest were policies and regulations of energy efficiency standards. Cost reduction was the highest rated factor that promotes energy efficiency practices. Practical implications: Occupants should be educated on energy efficiency through a change of their behaviours and also exposed to the benefits of using energy conservation measures. Management buy-in should be the goal of the facilities manager for the success of energy efficient practices. Originality/value: This study is an encompassing study on energy efficiency where many aspects of energy efficiency and factors that promote energy efficiency were explored.